Unilateral biportal endoscopic lumbar interbody fusion assisted by intraoperative O-arm total navigation for lumbar degenerative disease: A retrospective study - Huang, Xinle; Gong, Junfeng; Liu, Huan; Shi, Zegang; Wang, Wenkai; Chen, Shuai; Shi, Xiaobing; Li, Changqing; Tang, Yu; Zhou, Yue (Frontiers in Surgery, 2022)
Background: Recently, unilateral biportal endoscopic lumbar interbody fusion (BE-LIF) has been successfully applied for degenerative diseases of the lumbar spine, with good clinical results reported. However, the drawbacks include radiation exposure, limited field of view, and steep learning curves. Objective: This retrospective study aimed to compare the results between navigation and non-navigation groups and explore the benefits of BE-LIF assisted by intraoperative O-arm total navigation. Methods: A total of 44 patients were retrospectively analyzed from August 2020 to June 2021. Perioperative data were collected, including operative time, estimated intraoperative blood loss, postoperative drainage, length of hospital stay, radiation dose, and duration of radiation exposure. In addition, clinical outcomes were evaluated using postoperative data, such as the Oswestry Disability Index（ODI）, visual analog scale（VAS）, modified MacNab criteria, Postoperative complications and fusion rate. Results: The non-navigation and navigation groups included 23 and 21 patients, respectively. All the patients were followed up for at least 12 months. No significant differences were noted in the estimated intraoperative blood loss, postoperative drainage, length of hospital stay, fusion rate, or perioperative complications between the two groups. The radiation dose was significantly lower in the navigation group than in the non-navigation group. The average total operation time in the navigation group was lower than that in the non-navigation group (P<0.01). All clinical outcomes showed improvement at different time points postoperatively, with no significant difference noted between the two groups (P>0.05). Conclusions: Compared with the non-navigation approach, O-arm total navigation assistive BE-LIF technology not only has similar clinical results, but also can provide accurate intraoperative guidance and help spinal surgeons achieve accurate decompression. Furthermore，it can reduce radiation exposure to surgeons and operation time ，which improve the efficiency and safety of surgery.